Kampanye Penggunaan dan Pembagian Masker Sebagai Upaya Pencegahan Penularan Covid 19 di Pasar Landungsari Malang - Misbahul Subhi; Irfany Rupiwardani (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Currently, public awareness to use masks has begun to loosen, and people tend to ignore health protocols when doing activities outside the home, one of which is when shopping at the market, because we want to raise public awareness about the importance of implementing health protocols to prevent the spread of Covid 19 through the campaign. use and distribution of masks. The results obtained during this activity were traders who were very enthusiastic about asking about Covid, traders who asked for masks more than rations, and masks that were all used up and this activity received support from market managers well. The conclusion is that activities depend on assumptions, but there is still a need for continuous guidance and supervision by involving related parties.